Analisis Kualitas Bahan Bakar Marine Fuel Oil (MFO) Hasil Separasi pada Pembangkit Listrik Tenaga Diesel PT. Cogindo Daya Bersama – Kupang NTT - Filisianus Lende; Ishak S. Limbong; Wenseslaus Bunganaen (Universitas Nusa Cendana, 2025)
Analysis of the quality of marine fuel oil (MFO) from the separation process at the diesel power plant of PT. Cogindo DayaBersama Tenau is needed to increase the calorific value of the MFO. Tests were conducted using a bomb calorimeter to calculate the energy capacity value, a centrifuge to determine the sediment volume, and observations made using a microscope to investigate the particles in the MFO. The test results (using a bomb calorimeter) showed that the energy value of the MFO that had not been separated and that had been separated was 7,776 cal/g and 8,298 cal/g (6.71% greater). The test results (using a centrifuge) also showed that the average sediment volume value of the MFO fuel that had not been separated and that had been separated was 6,273 cm³ (96.67% sediment) and 0.216 cm³ (3.33% sediment). Microscope observations showed that separated MFO was superior to unseparated MFO, as it contained more particles than unseparated MFO. These results indicate that the MFO separation process at PT Cogindo Daya Bersama has been carried out effectively